Implementation of Preservation Policies amid Industrialisation: A Study of the Challenge of Cultural Heritage Area Degradation in Kampung Tugu - Siti Nur Laila Basir (Indonesian Scientific Publication, 2025)
This study examines the implementation of cultural heritage preservation policies in Kampung Tugu amidst industrialization that threatens its sustainability. This study used a qualitative method with a descriptive approach; data were collected through interviews with the North Jakarta City Administration Culture Office and the Kampung Tugu community, field observations, and literature studies. Data analysis was conducted using Van Meter and Van Horn’s policy implementation theory, evaluating policy standards, resources, implementer characteristics, inter-organizational communication, implementer disposition, and the socio-economic and political environment. The findings indicate that policy implementation has not been fully effective. While the government has made efforts to develop Kampung Tugu as a Tourism Village through initiatives such as the Living Museum and Keroncong music groups, land use changes and industrialization continue to degrade the area. Key obstacles include overlapping regulations, lack of inter-agency coordination, and inconsistent government leadership. The local community plays a significant role in preservation efforts but struggles with land rights and environmental challenges. The study concludes that although legal frameworks support heritage preservation, economic interests often take precedence, hindering effective policy execution. This research provides insights for policymakers, academics, and communities on the complexities of cultural heritage preservation in the face of urban development, and it highlights the need for future studies to integrate economic perspectives to ensure the sustainability of Kampung Tugu.